2013
DOI: 10.1186/1471-2474-14-100
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between health promoting resources and work participation in a sample reporting musculoskeletal pain from the Nord-Trøndelag Health Study, HUNT 3, Norway

Abstract: BackgroundMusculoskeletal pain (MSP) is one of the most frequent causes of sick leave from work, and is a common and potentially disabling condition. This study is based on the salutogenic perspective and investigates the relationship between personal, social, and functional health resources and work participation in a population reporting MSP.MethodAnalysis was performed on cross sectional data from the Nord-Trøndelag Health Study, HUNT 3, in Norway. The sample of n= 6702 was extracted from HUNT 3, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…However, in Salvador, Bahia, incapacitating RSI/WRMD has removed more women (66.9%) than men 2 from their work positions. In Norway, 65.1% of the absences involved female workers 12 . In Sweden and Japan, the female gender was associated with absence from work due to occupational pathologies 13,14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in Salvador, Bahia, incapacitating RSI/WRMD has removed more women (66.9%) than men 2 from their work positions. In Norway, 65.1% of the absences involved female workers 12 . In Sweden and Japan, the female gender was associated with absence from work due to occupational pathologies 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…In general, the occupations that expose workers to handling heavy loads, repetitive movements and long periods of static positions lead to higher risks of RSI/WRMD and subsequent absenteeism 19 . In relation to the anatomic site, a study from Norway showed the main causes of absenteeism were shoulder and cervical injuries 12 . In Salvador, Bahia, a study about the incidence of MSD showed that the diagnoses that mostly caused absence from work were synovitis/ tenosynovitis and shoulder injuries 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In a Korean study, employees with workplace violence experiences had a four times higher risk of sleep disorders compared to employees without such experiences [6], and another study associated such experiences with sleep problems among women [7]. Mental and physical health problems caused by workplace violence are often interconnected, and workers with workplace violence experiences have been found to maintain higher levels of tension while working, increasing their chances of poor physical health, including musculoskeletal pain [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Among people with musculoskeletal pain, there is a statistically significant relationship between work participation and health resources such as self‐reported health, feeling strong and absence of neuroticism, work control, workload and work participation (Sivertsen, Lillefjell, & Espnes, ). A review showed that perceived low physical disability and low emotional distress are associated with staying at work (de Vries, Reneman, Groothoff, Geertzen, & Brouwer, ).…”
Section: Introductionmentioning
confidence: 99%